2008
DOI: 10.1136/tc.2007.023812
|View full text |Cite
|
Sign up to set email alerts
|

What happened to smokers’ beliefs about light cigarettes when “light/mild” brand descriptors were banned in the UK? Findings from the International Tobacco Control (ITC) Four Country Survey

Abstract: The findings reveal that high levels of misperceptions about light cigarettes existed among smokers in all four countries before and after the EU ban took effect. We cannot conclude that the policy of removing some aspects of misleading labels has been effective in changing beliefs about light cigarettes. Efforts to correct decades of consumer misperceptions about light cigarettes must extend beyond simply removing "light" and "mild" brand descriptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 19 publications
10
84
3
Order By: Relevance
“…Research has repeatedly shown that although many smokers are not able to recall the specific tar level of their brand, a substantial proportion nevertheless equate lower numbers with a reduction in exposure and risk, and many use these numbers to guide their choice of brands (O'Connor et al 2006b). These findings are consistent with the ways in which smokers have been shown to perceive emission numbers when conveyed through advertising (Borland et al 2004(Borland et al , 2008Cummings et al 2004Cummings et al , 2006aHammond 2008a,b;King & Borland 2005;O'Connor et al 2006bO'Connor et al , 2007Shiffman et al 2001). Given the current scientific consensus that emissions data do not accurately reflect meaningful differences in risk between conventional cigarette brands, the World Health Organization (WHO) has called for the removal of emission numbers from packages (Hammond 2008a,b;World Health Org.…”
Section: Product Controls Product Controls Includesupporting
confidence: 75%
See 2 more Smart Citations
“…Research has repeatedly shown that although many smokers are not able to recall the specific tar level of their brand, a substantial proportion nevertheless equate lower numbers with a reduction in exposure and risk, and many use these numbers to guide their choice of brands (O'Connor et al 2006b). These findings are consistent with the ways in which smokers have been shown to perceive emission numbers when conveyed through advertising (Borland et al 2004(Borland et al , 2008Cummings et al 2004Cummings et al , 2006aHammond 2008a,b;King & Borland 2005;O'Connor et al 2006bO'Connor et al , 2007Shiffman et al 2001). Given the current scientific consensus that emissions data do not accurately reflect meaningful differences in risk between conventional cigarette brands, the World Health Organization (WHO) has called for the removal of emission numbers from packages (Hammond 2008a,b;World Health Org.…”
Section: Product Controls Product Controls Includesupporting
confidence: 75%
“…These variables have been demonstrated to predict smoking behavior and changes in smoking behavior (e.g., quitting). They include variables such as attitudes, normative beliefs, and intentions, and are taken from well-known psychosocial models of health behavior such as the Theory of Planned Behavior (Ajzen 1991), Social Cognitive Theory (Bandura 1986), the Health Belief Model (Becker 1974), and Protection Motivation Theory (Rogers & Prentice-Dunn 1997). In this conceptual model, policies affect these general mediator variables indirectly, via their prior effects on the more policy-specific variables.…”
Section: Conceptual Framework For Tobacco Control Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that punishing teens for purchasing, possessing, and using tobacco is ineffective, that it does little more than endorse the tobacco industry's marketing dodge of proclaiming that smoking is only for adults (12,13). Clean indoor air laws, (14)(15)(16)(17)(18) increased taxation, (19) forbidding the use of such deceptive cigarette descriptors as "light" (20) and warning labels (21)(22)(23)(24) have had significant effects, decreasing the prevalence of smoking. We are better at identifying smoking addiction (25).…”
Section: Cancer Prevention Today: Challenges For Preventionistsmentioning
confidence: 99%
“…Despite the fact that cigarettes described as "light" or "low tar" do not reduce health risks compared to regular brands, many smokers continue to believe that they are less harmful [1][2][3][4][5] . Filtervented "light" cigarettes ("lights") were initially introduced in Western countries to persuade increasingly health concerned smokers that they could reduce their health risks by smoking cigarettes that were apparently less harmful 6 .…”
Section: Introductionmentioning
confidence: 99%